Manual for guided home exercises for osteoarthritis of the knee - Carvalho, Nilza Aparecida de Almeida (2010)
INTRODUCTION: Physiotherapy is one of the most important components of therapy for osteoarthritis of the knee. The objective of this prospective case series was to assess the efficiency of a guidance manual for patients with osteoarthritis of the knee in relation to pain, range of movement , muscle strength and function, active goniometry, manual strength test and function. METHODS: Thirty-eight adults with osteoarthritis of the knee (>; 45 years old) who were referred to the physiotherapy service at the university hospital (Santa Casa de Misericórdia de São Paulo) were studied. Patients received guidance for the practice of specific physical exercises and a manual with instructions on how to perform the exercises at home. They were evaluated for pain, range of movement, muscle strength and function. These evaluations were performed before they received the manual and three months later. Patients were seen monthly regarding improvements in their exercising abilities. RESULTS: The program was effective for improving muscle strength, controlling pain, maintaining range of movement of the knee joint, and reducing functional incapacity. DISCUSSION: A review of the literature showed that there are numerous clinical benefits to the regular practice of physical therapy exercises by patients with osteoarthritis of the knee(s) in a program with appropriate guidance. This study shows that this guidance can be attained at home with the use of a proper manual. CONCLUSIONS: Even when performed at home without constant supervision, the use of the printed manual for orientation makes the exercises for osteoarthritis of the knee beneficial.